Quantitative CT Analysis of Lung Features in Patients with Polymyositis/Dermatomyositis without Interstitial Lung Disease - He HEI; Kai YANG; Liyu HE; Yadan SHENG; Yaqi YAN; Bingjie ZHU; Yuting ZHANG; Jiayin TONG; Jingping ZHANG; Chenwang JIN (CT Lilun yu yingyong yanjiu, 2025)
Objective: This study aims to analyze the lung differences between patients with interstitial lung disease (ILD) and non-interstitial (Non-ILD) diseases related to polymyositis/dermatomyositis (PM/DM) and healthy controls through quantitative computed tomography (CT) parameters. The objective is to establish a theoretical basis for early diagnosis and timely treatment of the disease. Method: A retrospective collection was conducted on 391 PM/DM patients, from December 2014 to October 2023, at the First Affiliated Hospital of Xi’an Jiaotong University. A total of 197 patients, including 143 ILD patients and 54 Non-ILD patients, were included in the study cohort. Fifty-four healthy controls were included in a 1∶1 ratio based on age and gender. All chest HRCT images of the study subjects were imported into the “Digital Lung” analysis platform, and quantitative CT parameters such as lung volume, average lung density, and pulmonary vascular volume were measured for the entire lung and each lung lobe. The differences in CT quantitative parameters among the three groups were compared, and ROC analysis was performed. Results: The lung volume in the PM/DM-ILD group decreased compared to the PM/DM-Non-ILD group, except for the right upper lobe. The average density of the entire lung and each lobe increased compared to the PM/DM-Non-ILD group, and the difference was statistically significant; The blood vessel volume of the entire lung, left and right lungs, and lower lobes of both lungs in the PM/DM-ILD group decreased compared to the PM/DM-Non-ILD group, and the difference was statistically significant. The PM/DM-Non-ILD group revealed a statistically significant decrease in the volume of pulmonary blood vessels in all lungs and lobes compared to the healthy control group. ROC analysis showed that the right lower pulmonary vascular volume exhibited the highest AUC value in distinguishing PM/DM-Non-ILD from healthy controls and PM/DM-ILD from PM/DM-Non-ILD. Conclusion: Quantitative CT features of the lungs differ significantly among PM/DM-ILD patients, PM/DM-Non-ILD patients, and healthy control groups, indicating that quantitative CT is an objective and sensitive method for evaluating lung changes in PM/DM patients. Compared with the healthy control group, patients in the PM/DM-Non-ILD group showed a significant decrease in pulmonary vascular volume, indicating that pulmonary vascular volume may be a sensitive indicator for the early detection of pulmonary damage in PM/DM patients.